Linking a Medical Vocabulary to a Clinical Data Model using Abstract Syntax Notation 1 - Huff, S. M.; Rocha, R. A.; Solbrig, H. R.; Barnes, M. W.; Schrank, S. P.; Smith, M. (Methods of Information in Medicine, 1998)
We have created a clinical data model using Abstract Syntax Notation 1 (ASN.l). The clinical model is constructed from a small number of simple data types that are built into data structures of progressively greater complexity. Important intermediate types include Attributes, Observations, and Events. The highest level elements in the model are messages that are used for inter-process communication within a clinical information system. Vocabulary is incorporated into the model using BaseCoded, a primitive data type that allows vocabulary concepts and semantic relationships to be referenced using standard ASN.l notation. ASN.l subtyping language was useful in preventing unbounded proliferation of object classes in the model, and in general, ASN.l was found to be a flexible and robust notation for representing a model of clinical information.
Keywords: Clinical Data Model; Vocabulary Concepts; Object Classification